Contamination levels of selected organochlorine and organophosphate pesticides in the Selangor River, Malaysia between 2002 and 2003 - Leong, Kok Hoong; Tan, Benjamin L.L.; Mustafa, Ali Mohd (Elsevier, 2007)
In Malaysia, rivers are the main source of public water supplies. This study was conducted from 2002 to 2003 to determine the levels of selected organochlorine and organophosphate pesticides in the Selangor River in Malaysia. Surface water samples have been collected seasonally from nine sites along the river. A liquid-liquid extraction followed by gas chromatography-mass spectrometry technique was used to determine the trace levels of these pesticide residues. The organochlorine pesticides detected were lindane, heptachlor, endosulfan, dieldrin, endosulfan sulfate, o,p'-DDT, p,p'-DDT, o,p'-DDE and p,p'-DDE whereas for organophosphate pesticides, they were chlorpyrifos and diazinon. At the river upstream where a dam is located for public water supply, incidents of pesticide levels exceeding the European Economic Community Directive of water quality standards have occurred. Furthermore, the wetland ecosystems located at the downstream of the river which houses the fireflies community is being threatened by occasional pesticide levels above EPA limits for freshwater aquatic organisms. The occurrence of these residual pesticides in the Selangor River can be attributed to the intense agriculture and urban activity.